Autonomy of (vocational) schools as an answer to structural changes - Spöttl, Georg [Verfasser] (My University, 2008)
"In Europe a very intensive discussion is in full swing as to whether vocational schools should in future be guided and monitored by the state or whether they should be freed from state dependency. Within the framework of a number of pilot projects in German-speaking countries, vocational school centres are currently testing their autonomy. This article sketches out the discussion on a way forward." (Autorenreferat, BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; S 4.3 Steuerung; Berufsschule; Lernende Organisation; Bildungssteuerung